2016
DOI: 10.1177/1521025116678852
|View full text |Cite
|
Sign up to set email alerts
|

College and Career Readiness of Southeast Asian American College Students in New England

Abstract: This study discusses the college and career readiness among full-time Southeast Asian American college students in a 4-year public university in New England. Our study consisted of surveys (n ¼ 58) and focus groups (n ¼ 35), of secondgeneration (born in the United States) or 1.5-generation (immigrated as a youth) college students. While our participants were fairly strong academically, they still struggled to navigate college and many did not feel prepared for careers. We found some variability by majors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For example, Chen and Fouad () found that East Asian American students’ desire to honor their parents was predictive of educational success outcomes, including retention and persistence. However, Asian American students who perceived parental support as pressure found it very stressful, even when they were succeeding academically (Rahman & Witenstein, ; Samura, ; Uy, Kim, & Khuon, ). For example, AANAPI students indicated to Jill that family approval was contingent upon their success in school and career, which exacerbated their concerns about being “behind.” Thus, exploring with students how their families influence their academic and career decision making—and whether students perceive it as positive and/or negative at different times—is critical.…”
Section: The Role Of Family and Peersmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Chen and Fouad () found that East Asian American students’ desire to honor their parents was predictive of educational success outcomes, including retention and persistence. However, Asian American students who perceived parental support as pressure found it very stressful, even when they were succeeding academically (Rahman & Witenstein, ; Samura, ; Uy, Kim, & Khuon, ). For example, AANAPI students indicated to Jill that family approval was contingent upon their success in school and career, which exacerbated their concerns about being “behind.” Thus, exploring with students how their families influence their academic and career decision making—and whether students perceive it as positive and/or negative at different times—is critical.…”
Section: The Role Of Family and Peersmentioning
confidence: 99%
“…Academic and career conversations with family may also be challenging for some Asian American students because of intergenerational family conflict (Ghosh & Fouad, ; Uy et al., ). Some Asian American immigrant parents may not fully understand the U.S. college‐to‐career process and are not able to help their children navigate associated challenges (Mau, ; Uy et al., ). Thus, Poon () has suggested family‐based programs that expose parents to the broad range of academic and career opportunities available to their children.…”
Section: The Role Of Family and Peersmentioning
confidence: 99%
See 3 more Smart Citations